The Role of HR in Advancing Sustainability and CSR - Heri Siswantoro; Rachmad Ilham; Anisaul Hasanah (Lembaga Pengembangan Kinerja Dosen, 2025)
Many organizations continue to struggle with superficial sustainability initiatives, weak accountability frameworks, and limited involvement of Human Resource Management (HRM) in strategic decision-making. These persistent issues hinder efforts to create meaningful and lasting change in corporate culture. The purpose of this article is to examine how HRM can drive the development of a sustainable and socially responsible organizational culture through structured, measurable, and values-driven practices. Drawing on recent conceptual and empirical insights from HRM, CSR, and ESG literature, the analysis highlights how initiatives such as embedding environmental metrics into performance appraisals, aligning ethical leadership development with corporate codes of conduct, institutionalizing inclusive hiring systems, and facilitating employee-led CSR engagement directly influence cultural transformation. These HR interventions promote employee trust, internal cohesion, and reputational legitimacy while anchoring sustainability as a lived organizational value. To maximize effectiveness, HR must be integrated into sustainability governance structures, equipped with analytics capabilities, and supported by leadership in implementing systemic change. Future research should investigate the long-term cultural impacts of digital HR tools, cross-sector differences in HR-ESG integration, and the role of hybrid work models in advancing equity and inclusion. Establishing a sustainable corporate culture depends not on symbolic policies but on intentional HR strategies that link people systems to environmental, ethical, and social outcomes.